Pergeseran Makna Qital dalam al-Qur’an Prespektif Toshihiko Izutsu: Kajian Semantika Tafsir - Ahnaf Gilang Ramadhan; Alvian Bhakti Pamungkas (Studia Quranika, 2024)
In history, the term qitāl has existed for a long time, even long before the time of the Prophet Muhammad SAW and his message in the form of the Qur'an. Then Islam came to complement the previous teachings. However, in this recent era, lafazh qitāl, which is often interpreted as a war between two camps or groups, has given rise to a negative view of Islam. Namely, there are accusations regarding terrorist and radical teachings in the Islamic religion, this is due to a misunderstanding of understanding this lafazh. Then a question arises, Are the accusations made against Islam true? So this research aims to examine in more depth the meaning of lafazh qitāl from time to time using semantic theory so that it can refute existing accusations regarding Islamic teachings. To answer this question, this research uses a descriptive-analytical method related to the meaning of qitāl pronunciation from the perspective of Toshihiko Izutsu's semantic theory, thus this research produces that qitāl pronunciation from this era has experienced development. Namely, it can be seen that in pre-Qur'anic times this meant killing, then in the Koranic era, it meant war that was defensive or defensive, after the revelation of the commandment verse for war this word developed into attack to control or be offensive, and following existing boundaries. Then in the end, this form of war does not always mean taking up arms so that bloodshed occurs, but means war with ideology that divides Muslims